2019
DOI: 10.21203/rs.2.10405/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Breaking barriers: using the Behavior Change Wheel to develop a tailored intervention to overcome workplace inhibitors to breaking up sitting time

Abstract: Background: The workplace is a prominent domain for excessive sitting. The consequences of increased sitting time include adverse health outcomes such as cardiovascular disease and poor mental wellbeing. There is evidence that breaking up sitting could improve health, however, any such intervention in the workplace would need to be informed by a theoretical evidence-based framework. The aim of this study was to use the Behaviour Change Wheel (BCW) to develop a tailored intervention to break up and reduce workp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 48 publications
(61 reference statements)
1
17
0
Order By: Relevance
“…Users indicated that they preferred to use the standing workstation when completing work tasks which did not require high levels of concentration, such as sending emails. Specific work tasks associated with standing have also been indicated in other studies [ 22 , 25 , 40 ]. Moreover, a recent study found that people did not identify “sitting” as an activity in and of itself, but rather thought of sitting in relation to the task they performed (e.g.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Users indicated that they preferred to use the standing workstation when completing work tasks which did not require high levels of concentration, such as sending emails. Specific work tasks associated with standing have also been indicated in other studies [ 22 , 25 , 40 ]. Moreover, a recent study found that people did not identify “sitting” as an activity in and of itself, but rather thought of sitting in relation to the task they performed (e.g.…”
Section: Discussionmentioning
confidence: 85%
“…This might indirectly mirror a decrease in perceived productivity if these tasks were done standing. In other studies there have been indications that high focus work tasks are prioritised over the use of the standing option [ 40 ], or that sitting postures are not consciously experienced during high-focus work tasks [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations